UNDIAGNOSED PERFORATION OF SILENT DUODENAL ULCER : A CASE REPORT WITH REVIEW (Indian Internet Journal of Forensic Medicine and Toxicology, 2007)
This is a case report where one Malaysian Indian female in her early fifties died due to perforation of  duodenal ulcer. She was apparently well before and had attended hospital for minor complaint of gastritis on  the evening before her death. GIT perforation is an acute emergency, if diagnosis is missed then it  adversely affect the life of the patient. The treatment of perforation and peritonitis is very time consuming  and costly, and at times results in severe infection, peritonitis, adhesions, and shock. In some cases, even  sudden death do occur in few hours after perforation. In this case, patient died within hour of acute symptoms  due to shock. Fatality following peptic ulcer perforation usually takes variable time, which can range from  few hours to many days or week.
Keywords: Peptic ulcer; perforation; sudden death; chronic duodenal ulcer; peritonitis; perforated duodenal ulcer